2011
DOI: 10.1371/journal.pone.0017211
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the MBF Repressor Yox1p by the DNA Replication Checkpoint Keeps the G1/S Cell-Cycle Transcriptional Program Active

Abstract: BackgroundIn fission yeast Schizosaccharomyces pombe G1/S cell-cycle regulated transcription depends upon MBF. A negative feedback loop involving Nrm1p and Yox1p bound to MBF leads to transcriptional repression as cells exit G1 phase. However, activation of the DNA replication checkpoint response during S phase results in persistent expression of MBF-dependent genes.Methodology/Principal FindingsThis report shows that Yox1p binding to MBF is Nrm1-dependent and that Yox1p and Nrm1p require each other to bind an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
2
24
0
2
Order By: Relevance
“…Consistent with this finding, rhp51 + transcription was suppressed by the MBF co-repressors Yox1 and Nrm1, and DNA replication stress de-repressed and maintained MBF-mediated rhp51 + transcription beyond the G1/S transition. The transcription of rhp51 + was similar to that of cdc18 + , which was induced at the G1/S transition and maintained by DNA replication stress, as previously reported [8] and confirmed in the present study. Therefore, our findings support the idea that DNA replication stress de-represses MBF-dependent G1/S transcription at most, if not all, target genes.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with this finding, rhp51 + transcription was suppressed by the MBF co-repressors Yox1 and Nrm1, and DNA replication stress de-repressed and maintained MBF-mediated rhp51 + transcription beyond the G1/S transition. The transcription of rhp51 + was similar to that of cdc18 + , which was induced at the G1/S transition and maintained by DNA replication stress, as previously reported [8] and confirmed in the present study. Therefore, our findings support the idea that DNA replication stress de-represses MBF-dependent G1/S transcription at most, if not all, target genes.…”
Section: Resultssupporting
confidence: 92%
“…Caetano et al l . demonstrated that DNA replication stress induces rhp51 + transcription via phosphorylation of the MBF repressor Yox1p [8]. However, it is not known how DNA replication stress induces rhp51 + transcription, or whether MBF binding to MCB motifs in the rhp51 + promoter is critical for DNA replication stress-induced rhp51 + transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Nrm1, another component of the MBF complex, which acts as its co-repressor (Bastos de Oliveira et al, 2012) has been found to be downregulated under nitrosative stress. Nrm1 is required to load the repressor Yox1 onto the MBF complex and thus inhibiting MBF dependent transcription (Caetano et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of these MBF-responsive genes results from checkpoint signalling-dependent inhibition of the negative feedback loop that turns off G1–S transcription during G1-to-S phase transition. The checkpoint effector kinases Rad53 and Cds1 directly target and inhibit the main G1–S transcriptional co-repressor Nrm1 in budding yeast and Nrm1 and Yox1 in fission yeast 101,102,110114 (FIG. 3).…”
Section: G1–s Transcription and Genome Stabilitymentioning
confidence: 99%